LEAN SERVICE APPROACH TO THE MAINTENANCE PROCESS OF CONSUMER PACKING MACHINE AT PT. BFM - Santika Sari; Berliana Sihotang; Nur Fajriah; Akhmad Nidhomuz Zaman (Journal of Industrial Engineering Management, 2021)
PT.BFM is a leading wheat mill in Indonesia and is also the first and largest producer wheat flour producer in Indonesia. This factory is very concerned about the quality of its products so the engineer must provide services by maintaining the machine to meet customer demand and maintain product quality well. To maintain customer confidence on the part of the engineer certainly must pay attention to the process of maintaining the machine itself, because the machine used must have waste. This study aims to identify waste and provide recommendations for improvement that aim to reduce the waste that occurs. By using the Lean Concept approach which is more dominant towards Lean Manufacturing and Six Sigma, so that this research can combine waste reduction with quality control using the DMAIC stage. That way the machine maintenance process can improve efficiency and improve quality. The study began by describing the Big Picture Mapping and weighting of waste values based on a questionnaire using VALSAT. Waste was also identified using FMEA to calculate the critical value of waste then a recommendation for improvement was carried out using 5W + 1H. Calculation results from processing data from data that has been collected, it was found that the total processing time which was previously 76,895 seconds to 57,342,497 seconds. The results of Value Added Activity are 85.233%, Non-Necessary Value Adding is 8.67% and Non-Value Added is 6.10%. FMEA analysis results obtained that critical waste that needs improvement is waste waiting with a score of 160